Anak Berkebutuhan Khusus (ABK) Bukan Sampah dan Musibah di Sekolah Penyelenggara Pendidikan Inklusif (SPPI) - Rusmiyati . (Universitas Alma Ata, 2017)
Inclusion schools provide opportunities to all students of various backgrounds and conditions within a school system and try to discover and develop the potential of multiple students. In developing the potential of students is not only applied to the students special need but also not special need. For the purposes of developing inclusive education teaching, the special needs of learners need to identify and assess the benefits and constraints, as well as the needs of learners. In its capacity as an educator, academic assessment is the main task and function of the teacher. Therefore, teachers can do an academic assessment. But for other assessments such as medical assessment, psychological, of course must be done by professionals who competence in the field.The curriculum needed for learners with special needs is determined from the assessment results, whether a learner requires modification of the Learning Program Design (RPP) or Individual Learning Program (PPI). Curriculum development in inclusive settings includes duplication, modification, substitution and omission. Teachers in particular schools of inclusion should be provided with knowledge of inclusiveness for children with special needs. Sehinggan ABK can get optimal service.